How to Overcome Impotence of Environmental Law in the Age of Anthropocene: Foundations of Ecocentric Law - S. Plicanic (Московский журнал международного права, 2022)
INTRODUCTION. This scientific article discusses the reaosns for inefficiency (“impotence”) of modern environmental law as a normative reaction to the “destruction of Nature”. The scope of the destruction of Nature has been broadening. The environmental protection law has thus not influenced the resurrection of “destroyed Nature”.MATERIALS AND METHODS. Consistent with explanatory and theory–building research, the methods used are those of historical legal research as well as general scientific methods, such as analysis, synthesis, analogy, description, and deduction. RESEARCH RESULTS. The essential reasons for the current excessiveness (intemperance) of man's interaction with Nature (the reasons for the “destruction of Nature”) and/or reasons for the inefficiency of the modern environmental law should be sought for in the dominant anthropocentric cultural paradigm of the western cultures oriented towards an un-limited material progress. If anthropocentrism (exploitativeness) as the basis of human utilitarian interaction with nature has led to the “destruction of nature,” there is no doubt that the ecological reason remaining within the anthropocentric construction of Nature can not lead to its “resurrection”. Only the setting-up of the ecocentric construction of Nature may lead to the “resurrection” of Nature. This orientation must be followed by the nomos of the western cultures. A new law of nature on the basis of the new, ecocentric ontology and ethics is therefore necessary.DISCUSSION AND CONCLUSIONS. In this article, the basics of a new ecocentric legal philospohy as the foundation of modern environmental law have been proposed. The scientific realisation of man's equality in the network of co-dependent natural entities in the last decades shows man his initial position – that is his (equal) postition in Nature. The determination of the rules of conduct which man must respect in interaction with Nature implies an expansion of the idea of law itself (justice and correctness) towards the interaction between man and Nature and not only the interaction within human community. Consequently, the economic interaction has to be maintained within the framework ensuring the vitality of other biotic communities. Also, incorporation of Nature in the very essence of law inevitably triggers a redefinition of legal values. The natural equilibrium, i.e., the equilibrium of life (including human life) becoming a legal value, we could speak of the expansion of the legal subject, i.e. the expansion of values which are the subject of legal protection. The initial position of the natural equilibrium addresses the issue of relationship of the new legal value towards the existing fundamental legal values of the western cultures. The enforcement of the maintenance of natural equilibrium may also demand a limitation of another legally protected value, for example, the right to the freedom of movement or some other human right. The new value, i.e., the maintenance of natural equilibrium, must be incorporated in the “contracts of statehood”, that is in the constitutions of the western countries as one of main legal values, next to “freedom”,“democracy” and “private property”. The entry of Nature in the western (legal) value system is a conditio sine qua non for an efficient change in the legal order and, most importantly, for a change in man's attitude towards Nature in everyday's life.